1999
DOI: 10.1021/jp984336v
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Electrokinetic Charging in Liquid Microjets

Abstract: We have investigated the physicochemical basis of electrokinetic charge separation in methanol using micron-sized channel diameters under both turbulent and laminar flow conditions. Turbulent flow studies were conducted using a 40 μm diameter stainless steel aperture which had a channel length of 0.5 mm. Under these conditions, electrokinetic streaming currents arose from a charge stripping process in the region close to the aperture channel wall. The moving liquid removed the relatively weakly held charges fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…An electron ejected from a liquid is accelerated or decelerated depending on the surface charge of the liquid. A surface charge is generated when a liquid passes through a liquid beam nozzle [23,24]. The resulting electrokinetic streaming potential (Φ str ) is given by…”
Section: (B) Reduction Of Electrokinetic Streaming Potential and Calimentioning
confidence: 99%
“…An electron ejected from a liquid is accelerated or decelerated depending on the surface charge of the liquid. A surface charge is generated when a liquid passes through a liquid beam nozzle [23,24]. The resulting electrokinetic streaming potential (Φ str ) is given by…”
Section: (B) Reduction Of Electrokinetic Streaming Potential and Calimentioning
confidence: 99%
“…However, a liquid microjet is electrically charged, because the liquid flow shears off an electric double layer at the inner wall of a capillary nozzle to create unequal number densities of cations and anions in the mobile part of the flow (flow electrification). 3,4 In a previous study, 5 we showed that the electric potential of a liquid microjet of NaX solution (X = Cl, Br, and I) varies with the electrolyte concentration. A notable common feature of the variation was that the polarity of the potential reverses at around a concentration of 30 mM (Figure 1), suggesting that Na + plays a key role in determining the polarity.…”
Section: Abstract: Liquid Microjet | Fused Silica | Capillary Nozzlementioning
confidence: 92%
“…To suppress electrokinetic charging, 36–38 NaCl was added to the water to form a 25 mM solution. The 25th harmonic of the fundamental 790 nm produced by HHG in Ar at 6 kHz was monochromatized by the 900 gr/mm grating, giving 39.2 eV EUV photons.…”
Section: Beamline Performancementioning
confidence: 99%